Level of learning style and level of students' critical thinking at private higher learning institutions - Puteh, Baharuddin; Jais, Zurairah; Omar Mokhtar, Muhammad Yasin; Idris, Nor Ainee; Wan Othman, Wan Norhayati (Human Resource Management Academic Research Society, 2021)
Students who study at a higher learning institutions have been independent in acquiring knowledge delivered by lecturers. This is closely related to the learning style of a student. Learning style plays an important role in determining the level of understanding of a student in a certain field in a certain university. This is due to the accurate learning style, it can identify the suitable method and strategy used in achieving a successful academic level. The objective of this research is to identify the learning style of students. Besides that, it is also to identify whether there is significant difference in the students’ learning styles according to gender. Other than that, it is to identify the relationship of students’ learning style towards students’ critical thinking. The findings in this research showed positive signs in the effort in enhancing students’ learning ability in innovation where it needs students to have creative and critical thinking. The comparison towards critical thinking based on students’ gender showed that there is no significant difference of the level of critical thinking between male and female students. This means the critical thinking between male and female students are similar which is high.